Strategic approaches to cultivating anti-corruption values in primary education: A case study of SDN Blimbing Gudo Jombang - Ningrum, Effiana Cahya; Prastyaningsih, Yuliana Putri (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2024)
This study explores the strategies implemented by SDN Blimbing Gudo Jombang to cultivate anti-corruption values among primary school students. The school has introduced a structured moral education program guided by the principal, integrating anti-corruption principles into Civic Education (PPKn), daily routines, and school culture. Employing a descriptive qualitative approach, data were collected through interviews, observations, and documentation involving the principal, teachers, and students. The findings reveal that the principal plays a central role in directing and supervising character-building initiatives, particularly in promoting honesty, discipline, responsibility, hard work, independence, fairness, courage, and empathy. Anti-corruption values are instilled through subject integration, habituation practices, exemplary behavior by school personnel, and the implementation of a “honesty canteen” as a practical learning medium. The study also identifies supporting factors such as family environment, peer influence, curriculum design, and institutional policies, along with challenges including limited anti-corruption learning resources. This research contributes to the literature on character education by highlighting contextually grounded strategies that strengthen anti-corruption awareness at the primary education level and provides practical insights for schools implementing similar initiatives.